The Library of Babel: The Universe of Jorge Luis Borges - Montanaro Meza, Oscar (2000)
Inaugural lecture of the 2000 academic year by the Master Oscar Montanaro Meza with the theme La biblioteca de babel: El universo de Jorge Luis Borges.